Isolation and characterizaton of multidrug resistant Escherichia coli from hospital, dairy and student hall wastes (Chittagong University Journal of Biological Sciences, 2013)
In this investigation a total of 31 isolates of E. coli were isolated randomly from different samples to analyze the resistance pattern to the most frequently used antibiotics. Among these 31 isolates 17 were isolated from hospital, 9 from student hall and 5 from dairy farm wastes. The isolates from hospital wastes showed 100% resistance to ciprofloxacin and ampicillin, 94% to penicillin, 76% to tetracycline, 41% to gentamicin and 35% to chloramphenicol. In contrast, the isolates from dairy farm wastes showed 100% resistance to penicillin and ampicillin, 80% to ciprofloxacin, and 40% to tetracycline. On the other hand, among the isolates of hall wastes 66% showed resistance to penicillin and ampicillin, 55% against ciprofloxacin and 44% to tetracycline. However all the isolates of dairy farm and hall wastes were sensitive to gentamicin and chloramphenicol. DOI: http://dx.doi.org/10.3329/cujbs.v5i1.13366 The Chittagong Univ. J. B. Sci.,Vol. 5(1 &2):19-25, 2010